Deep Anterior Lamellar Keratoplasty After Previous Anterior Lamellar Keratoplasty to Improve the Visual Outcomes. Issue 5 (May 2021) - Sarnicola, Caterina; Sarnicola, Enrica; Cheung, Albert Y.; Panico, Edoardo; Panico, Claudio; Sarnicola, Vincenzo
Abstract : Purpose: To describe a series of patients who underwent deep anterior lamellar keratoplasty (DALK) after previous anterior lamellar keratoplasty (ALK) to improve their visual outcomes. Methods: This is a retrospective case series of 9 DALK eyes (9 patients) with a history of previous ALK and an unsatisfactory visual outcome. Surgery was performed in all cases at least 3 years after ALK. Cannula big bubble, air viscobubble, and manual dissection techniques were performed. Preoperative and postoperative best-corrected visual acuity, residual recipient bed thickness, and endothelial cell count were evaluated. Follow-up was at least 24 months for all eyes. Results: Two subtotal anterior lamellar keratoplasties (through 1 type 1 big bubble and 1 air viscobubble) and 7 manual dissection DALKs were achieved. A small rupture of the residual recipient bed occurred during 1 case, and it was managed without penetrating keratoplasty conversion. Mean best-corrected visual acuity improved from 0.64 to 0.09 logMAR. Postoperative residual recipient central bed thickness was less than 80 μm in all cases. No postoperative complications were recorded at the last follow-up (24–36 months postoperatively). Conclusions: Different DALK techniques can be successfully used to improve visual acuity in previous ALK eyes with an unsatisfactory visual outcome. Abstract : Supplemental Digital Content is Available in the Text.